JURIDICAL STUDY OF REPRESIVE LEGAL PROTECTION AGAINST THE CIRCULATION OF FAKE "PATENT" MEDICINE - Hanifah, Salma Nur; Kurniawati, Husni; Mungawanah, Novia (UNTAG Law Review, 2024)
Consuming medication is an effort to maintain and maintain health. The high demand for medicines and low consumer knowledge create opportunities for business actors to produce fake medicines. The aim of this research is to determine the causes of the spread of fake patent medicines as well as the legal protection for consumers regulated in law along with BPOM's efforts to prevent the spread of fake patent medicines. The research method used in this research is empirical juridical, the research specifications used are analytical descriptive with data collection techniques through direct research in the field, namely open interviews and literature studies. Based on the research results obtained, the causes of the circulation of counterfeit patent medicines in influenced by business actors and consumer factors. Repressive legal protection for consumers is regulated in the Consumer Protection Law Article 8 Paragraph 1 Letter (a), Law Number 17 of 2023 concerning Health Article 138, Article 140 and Article 142. Apart from that, it is also regulated in the Regulation of the Medicine Supervisory Agency and Food Number 34 of 2018 concerning Guidelines for Implementing Good Medicine Manufacturing Methods. The prevention efforts carried out by BPOM are carried out in two forms, namely pre-market control in the form of standardization and product evaluation and post-market control in the form of Communication, Information and Education (KIE).